The emergence of enhanced intelligence in a brain-inspired cognitive architecture - Schneider, Howard (Frontiers in Computational Neuroscience, 2024)
The Causal Cognitive Architecture is a brain-inspired cognitive architecture developed from the hypothesis that the navigation circuits in the ancestors of mammals duplicated to eventually form the neocortex. Thus, millions of neocortical minicolumns are functionally modeled in the architecture as millions of “navigation maps.” Investigation of a cognitive architecture based on these navigation maps has previously shown that modest changes in the architecture allow the ready emergence of human cognitive abilities such as grounded, full causal decision-making, full analogical reasoning, and near-full compositional language abilities. In this paper, additional biologically-plausible modest changes to the architecture are considered, and show the emergence of super-human planning abilities. The architecture should be considered as a viable alternative pathway towards the development of more advanced artificial intelligence, as well as giving insight into the emergence of natural human intelligence.